NILAI TUKAR NELAYAN LAMPARA DASAR DI KECAMATAN PEMANGKAT KABUPATEN SAMBAS - Agam, Beryaldi; Muslimah, Muslimah; Apriandi, Apriandi (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2023)
The high fisherman terms of trade has a significant effect on the welfare level of the fishing community. This study aims to determine the income and welfare level of mini trawler fishermen in Pemangkat City Village. The research was conducted using a descriptive research method located in Pemangkat City Village. This study used a sample of small fishermen using mini trawler fishing gear, totaling 53 respondents. The technique used to take the sample is non-probability sampling with purposive sampling method, the data obtained will be analyzed by the income formula and analysis of the fisherman terms of trade. The results showed that the income of mini trawl fishermen was Rp. 5,367,715 are categorized as very high income and the exchange rate of mini trawl fishermen shows an average of 1.208265 so that the level of community welfare is classified as prosperous and can meet the needs of life.